Femininos de montar - Uma etnografia sobre experiências de gênero entre drag queens - Santos, Joseylson Fagner dos (2012)
The paper presents a discussion about gender and body in the drag queens experience at Natal city (RN). From the different concepts that characterizes the identity processes on subjects who perform gender transformation (transvestites, transsexuals and female impersonators), the justification for studying the drag character is observed as a means to understand matters that are important when you take such a position. Therefore, there is a need for a linkage between the various concepts responsible for this definition, in addition to considering the historical and cultural process responsible for the creation of such categories, identities and stereotypes among these individuals. In this sense it will be possible to carry out a critical analysis on the different social loads present in each representation, and understand what is at stake in the attribution of classifications and terminologies that are applied to different expressions of metamorphosis. This ethnography considers the debate from a field research conducted at LGBT social establishments and other performance spaces of these people, verifying their dynamics in these places and investigating relationships between performers, personas and characters and also backstage scene in which they participate